Natural Disaster, International Solidarity, and the Representation of Others. Lessons from Haiti - Túlio Zille (Revista Internacional de Cooperación y Desarrollo)
This essay revisits the case of the earthquake that shook Port-au-Prince, Haiti—which completed ten years in January 2020—to discuss the enduring, and often unaccounted for, colonial links between representation and contemporary humanitarian practices that are present in different ways in both North-South (in this case, between US and Haiti) and South-South relations (Brazil-Haiti). Unlike conventional approaches to natural disasters, which tend to focus their object of study in one particular place and time, I would like to propose an approach that instead engages multiple spaces, temporalities and agencies. In the context of this critical approach, and as a background question, I invite us to ask: what does international solidarity mean? The result is a more complex lens with which to look at events that are likely to become more frequent, and to affect the socio-economically disadvantaged in disproportional numbers in the near future due to the climate crisis.